‘Sisyphus nobis ante oculos’ (Lucr. 3.995): the dissent between ‘imperium’ and ‘auctoritas’ in the Late Roman Republic - Sant’Angelo, Maria de Nazareth Eichler (Romanitas - Revista de Estudos Grecolatinos, 2016)
In the paper that follows, we propose an original interpretation about the section of De rerum natura that brings the myth of Sisyphus (3. 995-1002). Our reading departs from the increasingly unstable relationship of complementarity and reciprocal exclusion between auctoritas and potestas. Lucretius invokes the mythical character to warn of the need to prevent the refusal of imperium to high magistrates by the negative response coming from the gods. He reproaches the use of the auspicia by some branches of Roman elite committed with optimates political orientation. From his point of view, they would be seeking to frustrate the political program of leaders aligned with the intellectual tradition referred as “popularis”.